The value of family history in the diagnosis of hypersensitivity pneumonitis in children - Cardoso,Joana (2014)
Hypersensitivity pneumonitis (HP), or extrinsic allergic alveolitis, is an immunologically mediated disease resulting from the inhalation of organic substances that trigger an inflammatory response in the alveolar wall, bronchioles, and interstitium in susceptible individuals. Although HP is predominantly an occupational disease, seen in adulthood, cases in children have been described. The diagnosis of HP requires a high degree of suspicion. The treatment consists in avoiding contact with the antigen, and, in some cases, systemic corticosteroids might be necessary in order to prevent its progression to pulmonary fibrosis. We report the clinical cases of three children with a history of contact with birds and a family history of HP. All three patients presented with cough and dyspnea on exertion. The disease was diagnosed on the basis of the clinical history and ancillary diagnostic test results consistent with the diagnosis, including a predominance of lymphocytes (> 60%, CD8+ T lymphocytes in particular) in bronchoalveolar lavage fluid and a ground-glass pattern seen on HRCT of the chest. Early diagnosis is crucial in order to prevent HP from progressing to pulmonary fibrosis. Hereditary factors seem to influence the onset of the disease.